Synthesis, Characterization, In-Vitro Antimicrobial and Antioxidant Activities of Co+2, Ni+2, Cu+2 and Zn+2 Complexes of 3-(2-(2-hydroxy-3-methoxybenzylidene)hydrazono)indolin-2-one - Zahid Khan,; Zahida T. Maqsood,; Muhammad Asad K. Tanoli,; Khalid M. Khan,; Lubna Iqbal ,; Mehreen Lateef, (Journal of Basic & Applied Sciences, 2015)
Four novel complexes of “3-(2-(2-hydroxy-3-methoxybenzylidene)hydrazono)indolin-2-one” have been synthesized with Co+2, Ni+2, Cu+2 and Zn+2. Physical and analytical techniques including CHN, IR, UV-Vis, AAS, molar conductivity values and magnetic susceptibility data were used to characterize all complexes. The bis Schiff base ligand i.e. 3-(2-(2-hydroxy-3-methoxybenzylidene)hydrazono)indolin-2-one, acted as a tridentate ligand and coordinated through phenolic oxygen, azomethine nitrogen and carbonyl group. Low values of molar conductance suggested the non-electrolyte nature of all complexes. Elemental analysis of complexes indicated the 1:1 metal to ligand mole ratios for [Cu(Inh)(OAc)] and [Zn(Inh)(OAc)] metal complexes and 1:2 metal to ligand mole ratios for [Co(Inh)2] and [Ni(Inh)2] metal complexes. Square planner geometry is proposed for [Cu(Inh)(OAc)] and distorted tetrahedral geometry is proposed for [Zn(Inh)(OAc)] while octahedral geometries are proposed for [Co(Inh)2] and [Ni(Inh)2] metal complexes. Antimicrobial and antioxidant studies were performed for all compounds and it was discovered that the complexes are more potent antibacterial and antifungal agents while the ligand exhibited comparatively more DPPH (1,1-diphenyl-2-picryl-hydrazil) radical scavenging activity than the complexes.